Optical and luminescence studies of ZnMoO4 using vacuum ultraviolet synchrotron radiation - Mikhailik, V; Kraus, H; Wahl, D; Ehrenberg, H; Mykhaylyk, MS (2006)
In this paper we present a characterisation of ZnMoO4 using spectroscopic techniques. Reflection, luminescence and luminescence excitation spectra were measured over the temperature range 8-295 K using VUV synchrotron radiation. The emission spectrum of the crystal exhibits a broad band with a maximum around 1.95 eV at 80 K that is attributed to the radiative transitions within MO42- oxyanion complex. An interpretation of the observed features of the electronic excitations in the crystal is given based on present knowledge of the electronic structure and emission properties of molybdate crystals. The results of this study suggest that ZnMoO4 is a suitable candidate for further testing for implementation as a target material in cryogenic scintillation searches for rare events. © 2006 Elsevier B.V. All rights reserved.